PENGGUNAAN MEDIA PEMBELAJARAN INTERKTIF TEMA BADAK BERCULA SATU MATERI EKOSISTEM UNTUK MEMENUHI KEBUTUHAN BELAJAR SISWA KELAS 5 SEKOLAH DASAR. - Ulinuha, Widda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the use of interactive learning media themed on the One-Horned Rhinoceros in the ecosystem subject to meet the learning needs of 5th-grade elementary school students. The media is designed to accommodate various learning styles, including visual, auditory, and kinesthetic, through the use of images, sounds, and motor activities. The research method used is qualitative with a case study approach, where data were collected through interviews, observations, and document analysis. The results show that the interactive learning media significantly improved students' understanding of the ecosystem material. The majority of students demonstrated full and partial comprehension through self-assessments provided by the media. Additionally, students with different learning styles felt more engaged in the learning process. Teachers also found the media beneficial as it helped convey complex material in a more enjoyable and interactive way. In conclusion, the interactive learning media themed on the One-Horned Rhinoceros effectively meets the learning needs of 5th-grade students, while also enhancing student engagement and understanding of the ecosystem material.